การคัดกรองความเสี่ยงการทุจริตโครงการก่อสร้างภาครัฐ: Screening for the Corruption Risk in Public Construction Projects - สุนทรานุรักษ์ สุทธิ (Journal of Applied Economics and Management Strategy, 2018)
ปัจจุบันมีงานวิจัยหลายชิ้นที่กล่าวถึงการคัดกรองความเสี่ยงการทุจริตโครงการก่อสร้างภาครัฐ บทความวิชาการนี้ได้สรุปสาระสำคัญจากงานวิจัยเรื่อง Corruption in the Construction of Public Infrastructure: Critical Issues in Project Preparation ของ Jill Wells (2015) ซึ่งเสนอแนวทางคัดกรองความเสี่ยงการทุจริตโครงการก่อสร้างภาครัฐโดยใช้ตัวแบบการบริหารจัดการลงทุนภาครัฐอย่างมีประสิทธิภาพ หรือ PIM Model ตัวแบบดังกล่าวอธิบายวิธีการคัดกรองความเสี่ยงที่อาจเกิดการทุจริตตั้งแต่ขั้นตอนการเตรียมโครงการ ทั้งนี้ ผู้ตรวจสอบสามารถนำตัวแบบนี้มาประกอบการพิจารณาจัดทำหลักเกณฑ์การตรวจสอบในการตรวจสอบเชิงรุกเพื่อป้องปรามความเสียหายได้อย่างทันกาล การสร้างหลักเกณฑ์ดังกล่าวเป็นการพัฒนาสัญญาณเตือนภัยโครงการเบื้องต้นเพื่อจะคัดกรองโครงการที่อาจมีความเสี่ยงที่จะเกิดทุจริต There has been numerous research papers about screening for the corruption risk mitigation in public construction projects. This article summarized main ideas from the research titled “Corruption in the construction of public infrastructure: Critical issues in project preparation” by Jill Wells (2015) which proposed the efficient public investment management model (PIM Model) to screen for the corruption in public construction projects. The model described corruption screening method starting from project preparation stage. The auditor could apply this model to create the guideline for proactive monitoring to timely mitigate damages from corruptive practices. This guideline was able to be developed to provide the early warning system to screen for the corruption risk in public construction projects.